1997
DOI: 10.1038/bjc.1997.363
|View full text |Cite
|
Sign up to set email alerts
|

Role of reactive oxygen species in cis-dichlorodiammineplatinum-induced cytotoxicity on bladder cancer cells

Abstract: Summary This study was undertaken to investigate the intracellular induction of reactive oxygen species (ROS) by cis-dichlorodiammineplatinum (CDDP) and the augmentation of their cytotoxicity in bladder cancer cells (KU7) by enhancement of ROS generation by the glutathione (GSH) depletors buthionine sulphoximine (BSO) and diethylmaleate (DEM). CDDP-induced cytotoxicity in KU7 cells and its modulation by GSH depletors were determined using spectrophotometric measurement with crystal violet staining. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(112 citation statements)
references
References 25 publications
7
101
0
2
Order By: Relevance
“…These findings are in agreement with other findings demonstrating that ROS is closely associated with cisplatin-induced apoptosis. [6][7][8][9] Our data also showed that cisplatin treatment induced the loss of MMP. Likewise, overexpression of Bcl-2 blocked cisplatininduced MMP loss and protected HN4 cells from both caspase-dependent and caspase-independent apoptosis induced by cisplatin treatment.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…These findings are in agreement with other findings demonstrating that ROS is closely associated with cisplatin-induced apoptosis. [6][7][8][9] Our data also showed that cisplatin treatment induced the loss of MMP. Likewise, overexpression of Bcl-2 blocked cisplatininduced MMP loss and protected HN4 cells from both caspase-dependent and caspase-independent apoptosis induced by cisplatin treatment.…”
Section: Discussionsupporting
confidence: 60%
“…Indeed, increased generation of ROS is closely associated with cisplatin-induced apoptosis. [6][7][8][9] ROS have been reported to activate the mitochondrial permeability transition, resulting in mitochondrial membrane potential (MMP) loss. 10,11 Loss of the MMP is considered to be involved in the apoptotic process induced by chemotherapeutic drugs [12][13][14] and can induce the release of potentially apoptogenic proteins such as cytochrome c, apoptosis-inducing factor (AIF) and endonuclease G (EndoG) from the intermembrane space.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of cells to CDDP or to other anticancer agents can induce the production reactive oxygen species (ROS) (Benhar et al, 2001;Miyajima et al, 1997;Simizu et al, 1998). In our previous study we demonstrated that CDDP-induced activation of JNK and p38 MAPKs was dependent on the production of ROS (Benhar et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatininduced cytotoxicity has been associated with the generation of ROS in cells. (33,34) The cisplatin-induced accumulation of ROS was found to be markedly suppressed in the inherently cisplatin-resistant HT-29 colon adenocarcinoma cell line. (35,36) In addition, the antitumor activity of HDAC inhibitors has also been associated with their ability to induce the intracellular accumulation of ROS.…”
Section: Hdac Inhibitors Potentiate Induction Of Apoptosis By Cisplatinmentioning
confidence: 99%